The Impact of Telenursing on Self-Care Management and Quality of Life for Chronic Disease Management Program (PROLANIS) Members with Type 2 Diabetes Mellitus at the Garuda Health Center in Bandung City, Indonesia, in 2022 - Purwanti, Tentry Fuji; Katmini, Katmini (Asian Journal of Health and Applied Sciences, 2023)
Diabetes Mellitus (DM) type 2 is rapidly becoming one of the world's most common non-communicable diseases (NCDs), and one of the most frightening problems in public health. Patients with type 2 diabetes mellitus must be able to manage their disease independently to control blood glucose and prevent complications. Community empowerment and social engineering can be done by nurses through remote communication with patients via telenursing. Identifying the Effect of Telenursing on Self-Care Management and Quality of Life for Members of the Chronic Disease Management Program (PROLANIS) with Type 2 Diabetes Mellitus. Using the pre-experiment design method with one group pretest-posttest design. The research sample consisted of 45 respondents, 15 male respondents and 30 female respondents, taking the sample using accidental sampling. Data collection using the Summary of Diabetes Self Care Activities (SDSCA) and Diabetes Quality of Life (DQOL) instruments the test used is the Wilcoxon Signed Ranks Test. All manuscripts must contain an abstract, which summarizes the purposes of the work, the methods, the most significant results, and the conclusions. Based on the results of the Wilcoxon test, with a 95% confidence level p-value (0.001). There is an effect of telenursing therapy on improving the quality of life of PROLANIS members with type 2 diabetes mellitus. It is hoped that respondents and elders can improve self-care management and quality of life through the stages of Diabetes Self-Management Education (DSME), which can be carried out daily under health workers’ guidance through telenursing or family.